Yahoo Web Search

  1. ( r - s)(x) = r (x) - s(x) = x - 4 - 3x² ( r s)(x) = r (x) s(x) = x - 4 3x² ( rs )(-2) = r (-2) * s(-2) = (-2 - 4)(3(-2)²) = (-6)(3 * 4) = -6 * 12 = -72 I hope this helps!

    2 Answers · Science & Mathematics · 16/12/2016

  2. First , prove C(n, r ) = C(n-1, r ) + C(n-1, r -1) . Assume there are n ... not included in chosen numbers then C(n-1, r ) ways exist because we must choose r numbers out of 2~n . If...

    1 Answers · Science & Mathematics · 26/10/2017

  3. (1 + r √(s - 6)) / ( r + √(s - 6)) = z (1 + r √(s - 6)) = z( r + √(s - 6)) 1 + r √(s - 6) = rz + z√(s - 6) r √(s - 6) - rz = z√(s - 6) - 1 r (√(s - 6) - z) = z√(s - 6) - 1 r = (z√(s - 6) - 1) / (√(s - 6) - z) ♣♦

    1 Answers · Education & Reference · 30/08/2011

  4. (1 - r ^4)/(1 - r ) = 1 + r + r ^2 + r ^3 LS = [(1 - r ^2)(1 + r ^2)]/(1 - r ) = [(1 - r )(1 + r )(1 + r ...8) / (1 - r²) = 1 + r² + r ^4 + r ^6 LS = (1 - r ^8)/(1 - r ^2) = [(1 - r ^4)(1 + r ^4)]/(1 - r ^2) = [(1 - r ^2)(1 + r ^2...

    4 Answers · Science & Mathematics · 26/11/2017

  5. E = -A* r ^(-1) + B * r ^(-n) dE/dr = A* r ^(-2)-n*B* r ^(-n-1) = A/ r ^2-n*B/ r ^(n+1) = 0 A/ r ^2 = n*B/ r ^(n+1) r ^(n+1-2) = r ^(n-1) = n*B/A r = (n*B/A)^(1/(n-1...

    2 Answers · Science & Mathematics · 21/01/2009

  6. r ^16 = 32 r ^16 = 2^5 log r ^16 = log 2^5 16 log r = 5 log 2 log r = 5/16 log 2 log r = log 2^5/16 log r = log 32^1/16 r = 32^1/16

    5 Answers · Science & Mathematics · 02/03/2010

  7. ( r - s)(x) = r (x) - s(x) = x - 4 - 3x² ( r + s)(x) = r (x) + s(x) = x - 4 + 3x² ( rs )(-2) = r (-2) * s(-2) = (-2 - 4)(3(-2)²) = (-6)(3 * 4) = -6 * 12 = -72 I hope this helps!

    5 Answers · Science & Mathematics · 26/06/2011

  8. Since R is bounded by the circle (x - 1)^2 + y^2 = 1, converting this... ( r cos θ - 1)^2 + ( r sin θ)^2 = 1 ==> r ^2 - 2r cos θ = 0 ==> r = 2 cos θ. (Note this is traced out with θ in [0, π...

    1 Answers · Science & Mathematics · 08/09/2011

  9. Subtract 1 from both sides. This gives you r ^2 + 3r - 1 = 0. You can't factor this, so use completing the square...

    2 Answers · Science & Mathematics · 29/03/2010

  10. ln(q + r ) = q  •   r   ... product rule on right side, where: dq/dr = q'     (q...q + r  q' ... "cross multiply"          q' + 1 = (q + r ) • (q + r  q' )          q' + 1 = q² + qr q'  + r ...

    1 Answers · Education & Reference · 04/03/2013

  1. Try asking your question on Yahoo Answers